Case Series: Lumbar Cerebrospinal Fluid Drainage in Aneurysm Clipping - Bayu, Timor Krisna; Prandani, Muhammad Yogi; Farid, Anisa Fadhila; Adiyanto, Bowo (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Intracranial aneurysm rupture is a medical emergency often accompanied by subarachnoid hemorrhage (SAH), which requires immediate medical intervention to reduce the risk of morbidity and mortality. This case report provides an overview of lumbar cerebrospinal fluid drainage (LCFD) as a method to reduce increased intracranial pressure and prevent or treat hydrocephalus that can occur after SAH. It is done by inserting an epidural catheter in the subarachnoid lumbar. The effectiveness of LCFD is more significant in patients with MFS 3-4. This finding supports the use of LCFD in managing SAH aneurysm to improve patients’ prognosis. Management of this case involved meticulous preoperative evaluation, appropriate intraoperative intervention, and strict postoperative monitoring, including treatment of cerebral vasospasm that may arise as a complication of SAH. The results suggest that LCFD can successfully reduce complications and improve clinical outcomes in patients with ruptured aneurysms who have undergone aneurysm clipping. The success of this method emphasizes the importance of a multidisciplinary approach in the management of SAH to achieve optimal patient outcomes.